2017
DOI: 10.1002/14651858.cd011188.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroids for the treatment of Kawasaki disease in children

Abstract: Moderate-quality evidence shows that use of steroids in the acute phase of KD can be associated with improved coronary artery abnormalities, shorter duration of hospital stay and a decreased duration of clinical symptoms. High-quality evidence shows reduced inflammatory marker levels. There were insufficient data available regarding incidence of adverse effects attributable to steroids, mortality and long-term (> 1 year) coronary morbidity. Certain groups, including those based in Asia, those with higher risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 44 publications
2
63
0
Order By: Relevance
“…However, IVIG resistance occurs in up to 20%–40% of unselected cases and is associated with increased coronary complication rates 1 10. Recent studies and meta-analyses of all published studies have suggested that addition of corticosteroids to IVIG reduces the risk of CAA, particularly in high-risk patients 1 10 11. However, there is currently no reliable method to predict which patients are at risk of CAA and thus require additional treatment, as scoring systems that predict IVIG non-response in Japan have not been reliable in studies in the UK and North America.…”
Section: Introductionmentioning
confidence: 99%
“…However, IVIG resistance occurs in up to 20%–40% of unselected cases and is associated with increased coronary complication rates 1 10. Recent studies and meta-analyses of all published studies have suggested that addition of corticosteroids to IVIG reduces the risk of CAA, particularly in high-risk patients 1 10 11. However, there is currently no reliable method to predict which patients are at risk of CAA and thus require additional treatment, as scoring systems that predict IVIG non-response in Japan have not been reliable in studies in the UK and North America.…”
Section: Introductionmentioning
confidence: 99%
“…Glucocorticoids reduce the rates of CAA development when used in KD patients at high risk of being resistant to IVIG treatment (41,42). Verdoni and colleagues (7) reported a high rate of IVIG resistance in KD patients who presented during the COVID‐19 pandemic, as compared to that in a historical cohort of KD patients, which may suggest a role for glucocorticoids in MIS‐C.…”
Section: Resultsmentioning
confidence: 99%
“…Other treatment options that could be considered are use of corticosteroids. A cochrane review of 7 trials showed benefits of reducing cardiac complications by using steroids as adjunct therapy to IVIG early in the course of illness [ 14 ]. Use of steroids alone without IVIG has not been studied.…”
Section: Discussionmentioning
confidence: 99%